Efficient atomistic simulations of lateral heterostructure devices with metal contacts. (December 2022) - Shin, Mincheol; Jeon, Seonghyeok; Joo, Kanghyun
Abstract: In this work we present a highly efficient method to perform quantum transport simulations on atomistic devices with metal contacts. In particular, we consider lateral heterostructures of silicide/semi-conductor/silicide and metal/semi-metal/metal which are constructed by the first-principles density functional theory method. We show that large-sized heterostructure Hamiltonian can be effectively reduced, while not losing the accuracy in a practical sense, enabling highly efficient calculation of the electrical transport properties of the devices based on the non-equilibrium Green's function method. Highlights: Developed highly efficient method for lateral heterostructure simulations. Effectively reduced the Hamiltonian size of heterostructures with metallic contacts. Quantum transport calculation by the non-equilibrium Green's function method.